Does the intensity of dissociation predict antidepressant effects 24 hours after infusion of racemic ketamine or esketamine in treatment-resistant depression? A secondary analysis from a randomized controlled trial - Mariana V. F. Echegaray; Rodrigo P. Mello; Guilherme M. Magnavita; Gustavo C. Leal; Fernanda S. Correia-Melo; Ana Paula Jesus-Nunes; Flávia Vieira; Igor D. Bandeira; Ana Teresa Caliman-Fontes; Manuela Telles; Lívia N. F. Guerreiro-Costa; Roberta Ferrari Marback; et al. (Trends in Psychiatry and Psychotherapy)
Abstract Objective Ketamine and esketamine have both shown significant antidepressant effects in treatment-resistant depression (TRD) and conflicting evidence suggests that dissociation induced by these drugs could be a clinical predictor of esketamine/ketamine's efficacy. Methods This study is a secondary analysis of data from a two-center, randomized, controlled trial. Participants were randomly assigned 1:1 to receive an IV infusion of either esketamine (0.25 mg/kg) or racemic ketamine (0.50 mg/kg) over 40 minutes. Dissociative symptoms were assessed using the Clinician-Administered Dissociative State Scale (CADSS) 40 minutes following the beginning of the infusion. Variations in depression scores were measured with the Montgomery-Åsberg Depression Rating Scale (MADRS), which was administered before the intervention as a baseline measure and 24 hours, 72 hours, and 7 days following infusion. Results Sixty-one patients were included in the analysis. Examining CADSS scores of 15 or below, for every 1-point increment in the CADSS score, there was a mean change of −0.5 (standard deviation [SD] = 0.25; p = 0.04) of predicted MADRS score from baseline to 24 hours. The results for 72 hours and 7 days following infusion were not significant. Since the original trial was not designed to assess the relationship between ketamine or esketamine-induced dissociation and antidepressant effects as the main outcome, confounding variables for this relationship were not controlled. Conclusion We suggest a positive relationship between dissociation intensity measured with the CADSS and the antidepressant effects of ketamine and esketamine 24 hours after infusion for CADSS scores of up to 15 points.